Psychopharmacology of asiatic acid from centella asiatica :in vitro and in vivo study - Abd Rahman, Izani Ghani
Centel/a Asiatica has a reputation to restore declining cognitive function in traditional medicine. In this study, asiatic acid from triterpenoids groups isolated from C. asiatica were examined for in vitro Thin Layer Chromatography (TLC) by bioautographic acetylcholinesterase inhibitory activity, in vivo psycopharmacology of excitatory post synaptic potential (EPSP} on the rat hippocampus and in vivo learning and memory potential as well as study of mechanism to the blood pressure with locomotors activities. This study is consistent with asiatic acid which having an effect on TLC bioautographic acetylcholinesterase inhibitory activity with minimal inhibition concentration, 0.125 llll· In vivo psycopharmacology of EPSP was shown selectively to GABA B receptor agonist. Then the inhibitory concentration was plotted using psycopharmacology of EPSP results with half maximal inhibitory concentration was 14 11M with Hill-Coefficient 0.9828. The in vivo learning and memory potential were performed using passive and active avoidance devices. Administration of asiatic acid facilitated on passive avoidance on memory but had no effect on active avoidance on learning. Study on mechanism to the blood pressure with locomotors performances shown that 10 dan 30 mg/k:g asiatic acid less effect in blood pressure and no sedative effect on locomotor performance.